Identifying business opportunities for green innovations: A quantitative foundation for accelerated micro-fuel cell diffusion in residential buildings - Justus von Geibler; Katrin Bienge; Dietmar Schüwer; O. Berthold; A. Dauensteiner; V. Grinewitschus; D. Hoffmann; W. Renner; Y. Ostermeyer (Energy Reports, 2018)
Combined heat and power (CHP) production in buildings is one of the mitigation options available for achieving a considerable decrease in GHG emissions. Micro-CHP (mCHP) fuel cells are capable of cogenerating electricity and heat very efficiently on a decentralised basis. Although they offer clear environmental benefits and have the potential to create a systemic change in energy provision, the diffusion of mCHP fuel cells is rather slow. There are numerous potential drivers for the successful diffusion of fuel cell cogeneration units, but key economic actors are often unaware of them. This paper presents the results of a comprehensive analysis of barriers, drivers and business opportunities surrounding micro-CHP fuel-cell units (up to 5 kWel) in the German building market. Business opportunities have been identified based not only on quantitative data for drivers and barriers, but also on discussions with relevant stakeholders such as housing associations, which are key institutional demand-side actors. These business opportunities include fuel cell contracting as well as the development of a large lighthouse project to demonstrate the climate-neutral, efficient use of fuel cells in the residential building sector. The next step could involve the examination and development of more detailed options and business models. The approach and methods used in the survey may be applied on a larger scale and in other sectors.
Keywords: 330; Fuel cells; Innovation barriers; Low-carbon buildings; Market survey